Sensory Feedback Training for Improvement of Finger Perception in Cerebral Palsy - Blumenstein, Tobias (Rehabil Res Pract, 2015)
Purpose. To develop and to test a feedback training system for improvement of tactile perception and coordination of fingers in children and youth with cerebral palsy. Methods. The fingers of 7 probands with cerebral palsy of different types and severity were stimulated using small vibration motors integrated in the fingers of a hand glove. The vibration motors were connected through a microcontroller to a computer and to a response 5-button keyboard. By pressing an appropriate keyboard button, the proband must indicate in which finger the vibration was felt. The number of incorrect responses and the reaction time were measured for every finger. The perception and coordination of fingers were estimated before and after two-week training using both clinical tests and the measurements. Results. Proper functioning of the developed system in persons with cerebral palsy was confirmed. The tactile sensation of fingers was improved in five of seven subjects after two weeks of training. There was no clear tendency towards improvement of selective use of fingers. Conclusion. The designed feedback system could be used to train tactile perception of fingers in children and youth with cerebral palsy. An extensive study is required to confirm these findings.